Political, Economic, and Social Life in Erzurum (1901-1904) - Emel Demir Görür (Yakın Dönem Türkiye Araştırmaları)
Erzurum is the only entrance gate of the important roads coming from the Caucasus and Iran to Anatolia. In antiquity and the Middle Ages, Erzurum was the main fortress that determined the destiny of the Anatolian defense against the armies that attempted to enter Anatolia from the east. Erzurum served as a base for the eastward movements of the Ottoman State for an significant portion of the early modern age, had been the main fortification of the state against attacks from Russia since the 19th century, and also suffered great damage in the Ottoman-Russian wars. In the last quarter of the 19th century and early 20th century, the activities of the Armenian committee members, as well as conflicts and natural disasters, adversely affected many aspects of the majority of the eastern provinces, including Erzurum. This study addresses the administrative, social, disciplinary, and economic statuses of Erzurum Province between 1901-1904 and in particular includes the province’s various judicial events, inter-tribal conflicts, income-expenditure items, mineral and forest resources, and public works. The article was prepared using documents from the Ottoman Archives and from the British Consulate, including the reports from Harry H. Lamp, Charles S. Hampson, and Avolon Shipley, who had been British Consuls in Erzurum.